High Levels of Perivascular Inflammation and Active Demyelinating Lesions at Time of Death Associated with Rapidly Progressive Multiple Sclerosis Disease Course: A Retrospective Postmortem Cohort Study - Owain Howell (Annals of Neurology, 2024)
Objective:Analysis of postmortem multiple sclerosis (MS) tissues combined with in vivo disease milestones suggeststhat whereas perivascular white matter infiltrates are associated with demyelinating activity in the initial stages,leptomeningeal immune cell infiltration, enriched in B cells, and associated cortical lesions contribute to disease pro-gression. We systematically examine the association of inflammatory features and white matter demyelination at post-mortem with clinical milestones.Methods:In 269 MS brains, 20 sites were examined using immunohistochemistry for active lesions (ALs) and perivenularinflammation (PVI). In a subset of 22, a detailed count of CD20+B cells and CD3+T cells in PVIs was performed.Results:ALs were detected in 22%, whereas high levels of PVI were detected in 52% of cases. ALs were present in35% of cases with high levels of PVI. Shorter time from onset of progression to death was associated with increasedprevalence and higher levels of PVI (bothp< 0.0001). Shorter time from onset of progression to wheelchair use wasassociated with higher prevalence of ALs (odds ratio [OR]=0.921, 95% confidence interval [CI]=0.858–0.989,p=0.0230) and higher level of PVI (OR=0.932, 95% CI=0.886–0.981,p=0.0071). High levels of PVI were associ-ated with meningeal inflammation and increased cortical demyelination and significantly higher levels of B lymphocyteswithin the PVI.Interpretation:ALs, a feature of early disease stage, persist up to death in a subgroup with high levels of PVI. Thesefeatures link to a rapid progressive phase and higher levels of meningeal inflammation and B-cell infiltrates, supportingthe hypothesis that chronic inflammation drives progression in MS.